Dengue outbreak in a city in the province of Buenos Aires; the importance of prevention and control of arboviral diseases in a non-endemic area (Actualizaciones en Sida e Infectología, 2025)
IntroductionDengue (DEN) is an arbovirus, and the emergence or re-emergence depends on the vector. In Argentina, Aedes aegypti is found in 17 provinces, including Buenos Aires (BsAs). Chivilcoy, located 160 km from the City of Buenos Aires, belongs to the province of Buenos Aires and Tenth Health Region. On 03/18/23, the first case of DEN without travel history (TH) was reported, followed by an increase in temporally and spatially related cases.The objective is to describe the clinical, biochemical, epidemiological and georeferencing characteristics of the DEN outbreak.Materials and methodsDescriptive study. Patients with Nonspecific Acute Febrile Syndrome were included between 02/22/2023 and 05/23/2023. The variables described: sex, age, TH, serotype, fever, headache, myalgia, clinical evolution, biochemical parameters and sections of the city. Data were collected from medical records and epidemiological records.ResultsFifty seven cases were diagnosed; 53 confirmed and 4 probable, with a cumulative incidence of 80.54 every 100,000 inhabitants. The median age was 33 (5-88). Without TH 70%. 88.6% serotype 1. Main symptoms: fever 95% and headache 72%. 7% required hospitalization. The possible index case (IC) was detected, who reported symptoms in epidemiological week (EW) 8 and TH. 75% of cases are located close to the IC.DiscussionIt is the first evidence of autochthonous circulation in Chivilcoy, and is also the only outbreak reported in the RSX. We worked early and articulately through vector control, tracking of feverish patients, IC search and georeferencing.
Keywords: dengue, acute febrile syndrome, fever, outbreak, arbovirus, Aedes aegypti, mosquito